Effects of thinning and heating for TiO2/AlInP junctions - J. Mäkelä; M. Tuominen; M. Yasir; V. Polojärvi; A. Aho; A. Tukiainen; M. Kuzmin; M.P.J. Punkkinen; P. Laukkanen; K. Kokko; M. Guina (Elsevier, 2022)
<span style="color: rgb(46, 46, 46); line-height: 23.68px; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24px;">TiO<sub style="margin: 0px; padding: 0px; border: 0px currentColor; border-image: none; color: rgb(46, 46, 46); line-height: 0; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 0.75em; word-spacing: -1.24px;">2<span style="color: rgb(46, 46, 46); line-height: 23.68px; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24px;">/AlInP junctions are used to construct the antireflection coatings for solar cells and to passivate III–V nanostructure surfaces. The thickness of AlInP epilayer affects light absorption and appropriate Al composition determining further the energy barrier for carriers. We report on reducing the AlInP thickness by dry etching down to 10 nm without introducing harmful defect states at TiO<sub style="margin: 0px; padding: 0px; border: 0px currentColor; border-image: none; color: rgb(46, 46, 46); line-height: 0; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 0.75em; word-spacing: -1.24px;">2<span style="color: rgb(46, 46, 46); line-height: 23.68px; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24px;">/AlInP interface and AlInP/GaInP interface below, according to photoluminescence. Synchrotron-radiation photoelectron spectroscopy reveals that increased oxidation of phosphorus is not harmful to TiO<sub style="margin: 0px; padding: 0px; border: 0px currentColor; border-image: none; color: rgb(46, 46, 46); line-height: 0; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 0.75em; word-spacing: -1.24px;">2<span style="color: rgb(46, 46, 46); line-height: 23.68px; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24px;">/AlInP and that post heating of the material enhances AlInP oxidation and group III element segregation resulting in decreased material homogeneity.